The phenomenological approach in psychological research.[article]. - Sta. Maria, Madelene .
The principles of the phenomenological approach are initially explained by examining how the use of introspection in the approach differs from its use as understood by the empirical psychologist. In phenomenology. it is assumed that subjectivity constitutes reality, and with this assumption we are given another viewpoint with which we may be objective about the mind. objectivity in a phenomenology study is to capture the invariance in the appearance of phenomena in consciousness or in subjectivity in varied circumstances of lived experience. Integral to this is the researcher's abandonment of the ' natural attitude' and the use of the researcher's own subjectivity in revealing meanings as a phenomenon is re-experienced through phenomenological analysis.